Respuesta :
Answer:
(x+9)(x-2)
Step-by-step explanation:
set the equation equal to 0. so x²+7x-18=0
x times x is x², 9 times -2 is -18, and 9 + -2 is 7
Answer:
solutions {-9, 2}
Step-by-step explanation:
Please, use " ^ " to denote exponentiation.
x^2+7x=18 should be rewritten in standard form as x2 + 7x - 18 = 0.
Note that (9)(-2) = -18, and that 9 - 2 = 7.
These results are helpful.
Thus, our x^2 + 7x - 18 = 0 factors as follows: (x + 9)(x - 2) = 0.
Setting each factor = to 0 separately, we get the solutions {-9, 2}